Land Use Pollution Potential of Water Sources Along the Southern Coast of South Africa - Malherbe Hanlie; Gebel Michael; Pauleit Stephan; Lorz Carsten (Change and Adaptation in Socio-Ecological Systems, 2018)
Since the 1990’s, the groundwater quality along the southern coast of the Western Cape Province of South Africa has been affected by increasing land use activities. Groundwater resources have become increasingly important in terms of providing good quality water. Polluted coastal groundwater as a source of submarine groundwater discharge also affects the quality of coastal water. For this study, land use activities causing groundwater pollution and areas at particular risk were identified. An assessment approach linking land use/land cover, groundwater and submarine groundwater discharge on a meso-scale was developed and the methods applied to two study regions along the southern coastal area. Dryland and irrigated crop cultivation, and urbanized areas are subject to a “high” and “very high” risk of groundwater nitrogen pollution. Application of fertilizer must be revised to ensure minimal effects on groundwater. Practice of agricultural activities at locations which are not suited to the environment’s physical conditions must be reconsidered. Informal urban development may contribute to groundwater nitrogen pollution due to poor waste water disposal. Groundwater monitoring in areas at risk of nitrogen pollution is recommended. Land use activities in the submarine groundwater discharge contribution areas was not found to have major effects on coastal water.